Health Outcomes of Unpaid Care Workers in Low-Income and Middle-Income Countries: A Protocol for a Systematic Review - Magana-Frade, I; Martinez-Diaz, P; Loyola-Fuentes, M (BMJ Publishing Group, 2018)
Introduction The literature on health outcomes of unpaid care work has included studies coming from high-income countries, and has reported gender inequalities that make caregiving women more vulnerable to physical and mental health problems. The impact of unpaid care work on the health of those living in low-income and middle-income countries, where women s autonomy is more limited, is unknown. Methods and analysis We will conduct a systematic review of observational studies on health outcomes according to unpaid caregiving status and sex of people living in low-income and middle-income countries. Cumulative Index to Nursing and Allied Health Literature, PubMed and Scientific Electronic Library Online Citation Index will be searched for reports in English or Spanish with published results from inception to 1 June 2017. We expect the studies to have recruited individuals in low-income and middle-income countries, including exposed and non-exposed groups to participation in unpaid care to members if their households or community reporting either physical and/or mental health problems, self-reported health-related quality of life, self-care skills/behaviours or use of any healthcare services in the participants. Data extraction, the assessment of risk of bias and confounding, and qualitative synthesis will be carried out by two independent reviewers with the assistance of a third party. Dissemination Results are expected to be published in peer-reviewed journals from the field of health and gender, or health and inequality. PROSPERO registration number CRD42017071785. © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2018. All rights reserved. No commercial use is permitted unless otherwise expressly granted.